2011
DOI: 10.1111/j.1875-595x.2011.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Indices for measuring periodontitis: a literature review

Abstract: Indices are important tools to measure, quantify and treat periodontitis both in epidemiological and clinical situations and are based on the prevailing understanding of the pathogenesis of periodontal disease. However, there is dearth of literature on collective information of periodontal indices formulated to date. This article collectively describes the evolution and the present concept of formulation of periodontal indices based on the multi-factorial nature of periodontal disease and also provides some di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 35 publications
(56 reference statements)
2
50
0
9
Order By: Relevance
“…The researchers recommend the use of clinical parameters such as GI, Pl, Izk, Ikon and NPE in order to establish precise anticipation and plan of periodontal therapy, and adequate monitoring of the achieved results [6][7][8][9][10] . Similarly, in this study the clinical parameters showed in all patients a low level of oral hygiene at the time of beginning of the study (Figures 1, 3 and 5) and an improvement in maintaining it one week after the applied therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers recommend the use of clinical parameters such as GI, Pl, Izk, Ikon and NPE in order to establish precise anticipation and plan of periodontal therapy, and adequate monitoring of the achieved results [6][7][8][9][10] . Similarly, in this study the clinical parameters showed in all patients a low level of oral hygiene at the time of beginning of the study (Figures 1, 3 and 5) and an improvement in maintaining it one week after the applied therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They are in the form of mouth rinses, gels, and they can be added to the toothpaste, too. The best known agents are chlorhexidine digluconate and fluorides [8][9][10] . Similarly, in this study the active ingredients of the Lacalut paste and solutions contributed significantly to the lower values of Pl.…”
Section: Mcdermid I Saradnicimentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing pupils from different CPITN registers the more common and treatable periodontal conditions: gingival bleeding, calculus and periodontal pocket 12 . However, when using teeth indices, the extent and severity of the illness may be underestimated 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The Community Periodontal Index of Treatment Needs (CPITN), recommended by the WHO 7 , is used for this purpose. It is to a standard measurement system used as an epidemiological tool for making comparisons between populations 8 .…”
Section: Introductionmentioning
confidence: 99%